The impact of COVID-19 on the format and nature of academic conferences in mathematics education - Engelbrecht, Johann; Kwon, Oh Nam; Borba, Marcelo C. [UNESP]; Yoon, Hyunkyoung; Bae, Younggon; Lee, Kyungwon (Springer, 2022)
The global COVID-19 pandemic has provided an opportunity to re-examine the possibility of organising virtual conferences in mathematics education, in which the social needs of participants can also be addressed. In this study we investigated the future impact that this change may have on the format and nature of mathematics education conferences. The study was conducted in two phases. We used an online questionnaire in which we asked participants to give us some input on the issues above. In the second phase of the project, focus group interviews were conducted with international mathematics education researchers. This study is an exploratory study, in which the sample was not developed in a way that could generate comparisons. The aim of the study was to raise possibilities about what may be the future of mathematics education conferences. Findings indicate that although academics are pro-actively thinking about alternative conference formats, the proven value of face-to-face conferences is still very real, showing that it is too early for us to have a clear vision of the future format of academic conferences.
Keywords: Academic conference; Mathematics education conference; Virtual conference; Face-to-face conference